2009
DOI: 10.1037/a0016488
|View full text |Cite
|
Sign up to set email alerts
|

Ethical challenges and opportunities at the edge: Incorporating spirituality and religion into psychotherapy.

Abstract: Incorporating spirituality and religion into psychotherapy has been controversial, but recent contributions have argued the importance and provided foundations for doing so. Discussions of ethical challenges in this process are emerging, and this contribution discusses several preliminary issues, relying on the Resolution on Religious, Religion-Based and/or Religion-Derived Prejudice adopted by the American Psychological Association in 2007, as guidance when used with the American Psychological Association's (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
108
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(108 citation statements)
references
References 32 publications
0
108
0
Order By: Relevance
“…A good question to ask might be: Would a third party payer be concerned if they knew the content of the intervention? (Gonsiorek, Richards, Pargament, & McMinn, 2009). …”
Section: Clearly Delineate Psychological Interventions With Religiousmentioning
confidence: 99%
“…A good question to ask might be: Would a third party payer be concerned if they knew the content of the intervention? (Gonsiorek, Richards, Pargament, & McMinn, 2009). …”
Section: Clearly Delineate Psychological Interventions With Religiousmentioning
confidence: 99%
“…As a matter of fact, even though, professionals' personal religious and spiritual views can serve as important components for expertise (meaning these views can influence their assessment of their patient's spiritual and religious issues, as well as the decision as to whether the use of religious and spiritual interventions is relevant), these are not sufficient or even necessary conditions for the competence (Plante, 2007;Gonsiorek, Richards, Pargament & McMinn, 2009;Gockel, 2011).…”
Section: Spiritual and Religious Competencies: Guidelines For Integramentioning
confidence: 99%
“…For instance, studying meditators in London, Lomas et al (2013) found that many only initially took up mindfulness as a stressmanagement technique; some were then perturbed to find it presented as including spiritual ideas and practices, and a few consequently disengaged from it as a result. As such, in whatever forum mindfulness is taught -from clinical/therapeutic settings to community groups -the notion of spirituality must be handled sensitively, with respect given to the divergent personal and cultural views people may hold regarding this (Gonsiorek et al, 2009). …”
Section: Therapeutic Implications Of Sampajaññamentioning
confidence: 99%